“It Is Really a Big Achievement for a Small Community Like the One of Curaçao.” Jan Greshoff (1888–1971) and De Stoep (1940–1951): An Exploration - Bant, Willem (Werkwinkel, 2016)
During the Second World War, both in the Dutch East Indies and in Curaçao, journals were published in which Dutch authors could publish their works unhampered by German censorship. In addition, literary works in Dutch were published in the Dutch East Indies, South Africa and New York. A man involved in all these initiatives was Jan Greshoff, an author who had played an important role in Dutch literature during the time between the two world wars. In this article, the role of Greshoff in relation to the literary journal De Stoep, which originated in Curaçao after the German occupation of Holland in 1940, will be explored. Although he never went to Curaçao and never met the journal’s founder, Luc. Tournier, in person, Greshoff played an important role in the history of De Stoep during the years of the war, and thus indirectly in the development of Dutch literature in Curaçao.